Renewable Resources, Pollution and Trade in a Small Open Economy - Horatiu A. Rus (Fondazione Eni Enrico Mattei (FEEM), 2006)
Industrial pollution can have damaging effects on resource-based productive sectors. International trade creates opportunities for overexploitation of the open-access renewable resources but also for separating the sectors spatially. The paper shows that, depending on the relative damage inflicted by the two industries on the environment, it is possible that the production externality will persist and that specialization in the dirty good may not be the obvious choice from a welfare perspective. Also, the resource exporter does not necessarily have to lose from trade even when specializing incompletely, due to the partially offsetting external effects.
Keywords: Q27; Q22; Q53; 330; Renewable Resources; Pollution; Production Externalities; Environment; International Trade